THEORETICAL AND METHODOLOGICAL BACKGROUND OF PHYSICAL EDUCATION OF PERSONALITY - Aleksandr Kudrya; Aleksandr Prostyakov; Dmitry Gladkikh (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the formation of personality through internalization - appropriation of the products of social experience in the field ofphysical culture in education and training, which is at the same time the external condition for the development of the subject of education certain positions, roles, functions and activities collectively characterizing its specific social and personal portrait.